Bringing College Classrooms to the Community: Promoting Post-Secondary Access for Low-Income Adults Through Neighbourhood-Based College Courses - Bourke, Alan; Vanderveken, Jim; Ecker, Emily; Atkinson, Jeremy; Shearer, Natalie (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2019)
In this paper we utilize interview data to explore the workings of a college– community partnership program that delivers tuition-free, for-credit courses to low-income adult students in neighbourhood-based settings. Addressing the interplay of individual and structural barriers on the educational readiness of students, our findings explore how the program builds participants’ confidence and self-belief, and how the neighbourhood-based delivery model encourages their engagement with post-secondary education (PSE). We find that the value of embedding PSE capacity and resources in low-income communities lies not only in its potential to engage adult learners, but also in how it nurtures a greater sense of community integration and social inclusion. We conclude by suggesting that our study provides a useful foundation for institutions elsewhere aiming to recalibrate and extend their community outreach strategies when seeking to promote post-secondary access and engagement for low-income populations.